Micro Mechanical Transducers - Pressure Sensors, Accelerometers and Gyroscopes - Bao, Min-Hang (Handbook of sensors and actuators, 2000)
Some years ago, silicon-based mechanical sensors, like pressure sensors, accelerometers and gyroscopes, started their successful advance. Every year, hundreds of millions of these devices are sold, mainly for medical and automotive applications. The airbag sensor on which research already started several decades ago at Stanford University can be found in every new car and has saved already numerous lives. Pressure sensors are also used in modern electronic blood pressure equipment. Many other mechanical sensors, mostly invisible to the public, perform useful functions in countless industrial and consumer products.